Black Pepper, Aloe-Vera and Turmeric: A Polyherbal Anti-Acne Remedy - Tajane, Monali; Sawant, Shubhangi; Londhe, Reshma (Journal of Drug Delivery and Therapeutics, 2019)
In the present research work ethanolic extracts of Black pepper (Piper nigrum), Turmeric (Curcuma longa) obtained by maceration and Aloevera gel (Aloe barbadensis) are mixed with a base to formulate a homogenized polyherbal cream formulation as a remedy against Acne would follow by the evaluation for its physical parameters like Colour and Odour, Consistancy, Homogeneity Washability, PH, Stability , Irritancy test etc.Keywords: maceration, antibacterial, antiacne